2019
DOI: 10.3390/tropicalmed4040131
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis among Hemodialysis Patients in Jordan: First Preliminary Screening Surveillance

Abstract: Few studies have reported the incidence of cryptosporidiosis among hemodialysis patients worldwide. Currently many molecular and immunological assays have been developed for the sensitive diagnosis of cryptosporidiosis, but still, the microscopic detection of the parasitic infective stage (oocysts) in stool specimens using modified acid stain is regarded as a reliable sensitive technique which is widely used in many clinical labs. In the present study, a total of 133 stool samples were collected from hemodialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…While, disagreement with [21] which recorded 17 (81%) among symptomatic children in Egypt by using nested PCR. There are two important species of Cryptosporidium that are responsible for human infection (C. parvum and C.hominis), it is a very important issue to determine the species of this protozoan in clinical cases even though the treatment could be identical, This differences in the percentage of C. hominis infection may due to the variation in the sample size for each study [22] The current study showed a higher percentage of positivity among females than males although there was no statistically significant association between positivity and gender of cryptosporidiosis patients these results were in agreement with the findings of [23] in Jordan which record no statistically significant association between cryptosporidiosis and gender among Hemodialysis Patients in Jordan by using M.Z.N stain also [24] in Pakistan registered no significant difference between cryptosporidium spp. and gender among children by using M.Z.N stain and disagreed with the result by [25] in Nigeria which recorded statistical significant between cryptosporidiosis and gender by using M.Z.N stain the variation in the rate of infection between males and females may be because females are more movement and active and their contact with the external environment factors, It may lead to a lack of attention to personal hygiene and wash hands which increase the chances of being infection [26] In the current study distribution of the Cryptosporidiosis infection according to residence by using M.Z.N stain, there was statistically significant association between positivity of cryptosporidiosis and residence p=(0.015) this results agreement with [27] in Beni-Suef, Egypt were recorded P-value= 0.03 in diarrheic Immunocompetent Patients and disagreement with [28] in Erbil City-Iraq were recorded no statistically significant association between positivity of cryptosporidiosis and residence among children from regular visitors of Raparin Hospital using M.Z.N stain.…”
Section: (25%) In Immunocompromised Patients Andsupporting
confidence: 85%
See 1 more Smart Citation
“…While, disagreement with [21] which recorded 17 (81%) among symptomatic children in Egypt by using nested PCR. There are two important species of Cryptosporidium that are responsible for human infection (C. parvum and C.hominis), it is a very important issue to determine the species of this protozoan in clinical cases even though the treatment could be identical, This differences in the percentage of C. hominis infection may due to the variation in the sample size for each study [22] The current study showed a higher percentage of positivity among females than males although there was no statistically significant association between positivity and gender of cryptosporidiosis patients these results were in agreement with the findings of [23] in Jordan which record no statistically significant association between cryptosporidiosis and gender among Hemodialysis Patients in Jordan by using M.Z.N stain also [24] in Pakistan registered no significant difference between cryptosporidium spp. and gender among children by using M.Z.N stain and disagreed with the result by [25] in Nigeria which recorded statistical significant between cryptosporidiosis and gender by using M.Z.N stain the variation in the rate of infection between males and females may be because females are more movement and active and their contact with the external environment factors, It may lead to a lack of attention to personal hygiene and wash hands which increase the chances of being infection [26] In the current study distribution of the Cryptosporidiosis infection according to residence by using M.Z.N stain, there was statistically significant association between positivity of cryptosporidiosis and residence p=(0.015) this results agreement with [27] in Beni-Suef, Egypt were recorded P-value= 0.03 in diarrheic Immunocompetent Patients and disagreement with [28] in Erbil City-Iraq were recorded no statistically significant association between positivity of cryptosporidiosis and residence among children from regular visitors of Raparin Hospital using M.Z.N stain.…”
Section: (25%) In Immunocompromised Patients Andsupporting
confidence: 85%
“…contaminated water, farm animals and wildlife) and presence of grazing such as cows and sheep in rural areas compared with urban areas [31] while regarding the prevalence of cryptosporidiosis infection and association with water source the current study shown that the highly infection appear in participant who used bottle water in compared among who used tap water when used M.Z.N stain and there was statistically significant association recorded by using PCR technical method between C.parvum and water source p=0.03. This result disagreement with [32] in Taiz which recorded high infection occur among participant who used tap water from children of different ages by using M.Z.N stain also [23] in Turkey were recorded results that disagreement and no statistical significant between C.parvum and water source p=0.33 among Immunosuppressive and Immunocompetent Cases with Diarrhea by using PCR. These variation in results may be due to The oocysts are very resistant to chlorine, chloramines, and chlorine dioxide, which are commonly used in methods of water system disinfection, and keep vital for infection in the environment for a long time [33] .…”
Section: (25%) In Immunocompromised Patients Andmentioning
confidence: 69%
“…The age of the patients ranged from 25 to 80 (mean 57.8; standard deviation 12.2) years and the most frequently reported symptoms were gastrointestinal symptoms. The study ensured the importance of modified acid-fast stain as a primary screening method and has recommended increasing the awareness of this parasite in this population group, and to include patients with kidney transplantation as well (12).…”
Section: Literature Reviewmentioning
confidence: 97%
“…The last published paper for cryptosporidiosis in Jordan was in October 2019 (12). This described the prevalence of cryptosporidiosis among haemodialysis patients from different areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation